2022
DOI: 10.3390/pathogens12010022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Utility of Simplicillium lanosoniveum, a Hyperparasitic Fungus of Puccinia graminis f. sp. tritici, as a Biological Control Agent against Wheat Stem Rust

Abstract: Wheat stem rust is one of the wheat diseases caused by Puccinia graminis Pers. f. sp. tritici (Pgt). This disease has been responsible for major losses to wheat production worldwide. Currently used methods for controlling this disease include fungicides, the breeding of stem rust-resistant cultivars, and preventive agricultural measures. However, the excessive use of fungicides can have various deleterious effects on the environment. A hyperparasitic fungus with white mycelia and oval conidia, Simplicillium la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Previously, numerous authors have reported S. lanosoniveum as a mycoparasite of rust fungi on coffee leaves, soybeans, wheat stems, and further plant species worldwide [8,14,29,30]. The results of surveys have suggested that the fungus has high potential to inhibit the growth and spread of rust diseases, indicating this species as an ideal candidate for biological control.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, numerous authors have reported S. lanosoniveum as a mycoparasite of rust fungi on coffee leaves, soybeans, wheat stems, and further plant species worldwide [8,14,29,30]. The results of surveys have suggested that the fungus has high potential to inhibit the growth and spread of rust diseases, indicating this species as an ideal candidate for biological control.…”
Section: Discussionmentioning
confidence: 99%